Caregiver experience in preventive treatment for children exposed to Human Immunodeficiency Virus - Silva, Mariana Ramos da; Alvarenga, Willyane de Andrade; Dupas, Giselle (Rev Rene, 2014)
This study aimed to understand the experience of caregivers of children vertically exposed to the Human Immunodeficiency Virus. It used Symbolic Interactionism as a theoretical framework. It is a qualitative research with data collection carried out in a reference clinic in a municipality in the state of São Paulo, from November 2012 to August 2013 through semi-structured interviews with 12 mothers and a grandmother. Data were analyzed using the Content Analysis method. The caregivers administered antiretroviral to child to prevent virus infection and perceived good acceptance of medication. The child was considered healthy and waiting for the test results generated suffering. Family support and public health services were highlighted as an aid to go through this route pervaded by prejudice, lack of direction, fear and inability to breastfeed. It was noted that the public health service in the city studied tried to follow the protocol requirements established, however, improvements in the quality of counselling is needed.